The Effect Of Celebrity Endorsers And Social Media Marketing On Purchase Decisions For Labubu Dolls, With Trust As A Mediating Variable - Qaulika, Lola Lubna; Roosdhani, Mohamad Rifqy (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Balikpapan, 2026)
This study's objective is to examine how celebrity endorsers and social media marketing influence consumers' decisions to purchase Labubu dolls, using trust as a mediating factor . This study stems from increased consumer interest in products promoted by public figures, especially after Lisa Blackpink's post, which boosted Labubu's popularity in Indonesia. This study employs a quantitative method processed using SmartPLS version 4.0 and involves 150 respondents who have chosen to buy Labubu dolls. The results show that consumer trust and purchase decisions are significantly impacted by social media marketing and celebrity endorsers. The trust variable mediates the impact of both on purchasing decisions, according to the significant p-value on the mediation path. These findings show that public figures and digital marketing strategies are very important for young consumers purchasing decisions.